Race, racism and development interrogating history, discourse and practice (London Palgrave Macmillan, 2012)
"Race, Racism and Development places racism and constructions of race at the centre of an exploration of the dominant discourses, structures and practices of development. Combining insights from postcolonial and race critical theory with a political economy framework, it puts forward provocative theoretical analyses of the relationships between development, race, capital, embodiment and resistance in historical and contemporary contexts. Exposing how race is central to development policies and practices relating to human rights, security, good governance, HIV/AIDS, population control, NGOs, visual representations and the role of diasporas in development, the book raises compelling questions about contemporary imperialism and the possibilities for transnational political solidarity."
Includes bibliographical references (p. [257]-279) and index.
Keywords: Racism -Economic aspects